HISTORICAL DEVELOPMENT OF THE ORANYAN CULTURAL FESTIVAL IN NEW OYO: A STRATEGIC MEASURE TO PRESERVE YORÙBÁ ANTIQUITIES IN THE 21ST CENTURY - OYEDOKUN MOJEED OYETUNJI; AKANBI SHOLA AHMED; ADEYEMI KAMIL HAMZAH (International Studies Journal)
This study investigated the different ways in which Yorùbá cultural indigenous identities are presented to the world in contemporary times through the Oranyan festivals. The Oranyan festival in New Oyo is a traditional celebration of Yorùbá heritage, with roots dating back to the late 14th century. The cultural festivals of Oyo Yorùbá are diverse, but the Oranyan festival is unique in New Oyo because of its global acceptance orchestrated by His Royal Highness, the Alaafin of Oyo, the late Oba Lamidi Adeyemi Olayiwola III. The festival is one of the special annuals that attracts people from different parts of the universe. The event, since its commencement, has uniquely portrayed Yorùbá cultural values, mainly to present Yorùbá cultural values from a historical perspective against Eurocentric views, and characterised by handmade attire, sculptures, liturgical objects and other traditional instruments. This paper gave an in-depth analysis of the historical development of the Oranyan festival among the Yorùbá and its impact on global assessment in the African past. The study used primary and secondary data to elicit information. Primary sources involved archival materials, structured questionnaires, and in-depth interviews with rural and urban dwellers. Secondary sources included texts, articles, and newspapers to complement data from primary sources. The finding shows that the Oranyan festival plays a critical role in the affirmation of African pantheon and preserving Yorùbá antiquities in the 21st century. The paper concludes that the continued practice and celebration of the festival are essential for preserving Yorùbá antiquities and promoting a sense of identity and cultural heritage.